P-794 Cadherin1 is essential for blastulation: a CRISPR-Cas9 knock-out approach in human embryos. (30th June 2022) - Ferrer, A; Pujol, A; Bello-Rodríguez, J; Rodríguez, A; Vassena, R; Tiscornia, G
Abstract: Study question: Is Cadherin1 required for human embryo blastulation? Summary answer: Knock-out of Cadherin1 by Crispr/Cas9 technology in human embryos impairs cavitation and blastula stability. What is known already: Embryo compaction involves an increase in intracellular adhesion mediated by E-cadherin. Concomitantly, the outer blastomeres undergo apical-basal polarization and are fated to generate the trophectoderm, the first epithelium of the embryo. Mice embryos devoid of E-Cadherin can complete compaction driven by maternal E-cadherin but fail to form a trophectodermal epithelium and a blastocoel. While mouse and human preimplantation development share common landmark events, there are also significant species-specific differences. To determine the role of Cadherin1 ( CDH1 ) in preimplantation development, the E-Cadherin gene was targeted using the Crisper-Cas9 system in human 3PN embryos. Study design, size, duration: This is a prospective basic research study; 64 tripronuclear zygotes (3PN) from patients undergoing IVF were collected between October 2018 and October 2019. 3PN zygotes were vitrified with pronuclei still visible, stored and warmed before processing. Participants/materials, setting, methods: 58 3PN zygotes survived warming and were injected either with an equimolar combination of 3 guides targeting exon 2 of CDH1 (200ng/ul) or a scrambled control guide, along with Cas9; 3PN development was monitored by time-lapse microscopy, taking time of ICSI as T = 0. Culture was stopped at D6 or when embryos arrested for 24h. Genomic DNA was obtained by Multiple Displacement Amplification. Amplicon sequencing of on- and off-targets was performed to evaluate targeting efficiency. Main results and the role of chance: 23 control and 29 treated 3PN embryos were successfully injected. In the control and treated group respectively, 10/23 (43.5%) and 15/29 (51.7%) embryos did not develop beyond the 8-cell stage; 1/23 (4.3%) and 3/29 (10.3%) embryos did not develop beyond the 16-cell stage; 4/23 (17.4%) and 3/29 (10.3%) embryos started to compact but failed to initiate cavitation. 8/23 (34.8%) and 8/29 (22.8%) started to cavitate (all differences non-significant, exact Fisher test). Interestingly, while 6/23 (26.1%) control embryos formed stable blastocysts, only 1/29 (3.4%) reached the stable blastocyst stage after CDH1 ablation (p = 0.035, exact Fisher test). To determine editing efficiency, we sequenced both the CDH1 exon2 and 7 off-target sites for each of the 3 guides used, in 6 control and 26 treated embryos. 14/26 (53.8%) of the treated embryos had severe disruptions, in CDH1 exon2, presenting up to 3 deletions and short indels between and around the guide sites in exon2, while 13/26 (46.2%) treated embryos were unaffected. Off-target sequences were unaffected in both groups. None of the edited embryos reached the blastocyst stage. Thus, loss of CDH1 compromises cavitation in developing human embryos, presumably by affecting cell-cell junctions and integrity of trophoblast cells, resulting in lower blastocyst rate formation. Limitations, reasons for caution: Embryos analyzed in the study arise from 3PN embryos; the observed phenotype may be partially due to chromosomal abnormalities, although the difference in frequency of blastocyst formation between control and treated groups suggests a small effect of the sample type on the observed CDH1 knock-out phenotype. Wider implications of the findings: We show that Cadherin 1 is necessary to reach a stable blastocyst stage in human preimplantation development, even though compaction and initial blastulation are possible. Further, our results confirm that 3PN embryos can be a useful model for testing gene function of candidate genes in human preimplantation development. Trial registration number: NA